Characterization Of The Noise And Vibration Patterns Of The Vehicle HVAC System Under Various Operating Condition - Hamdan, Muhammad Hidayat (Universiti Sains Malaysia, 2018)
Noise and vibration have imperative impact on customer perception of vehicle quality and cabin interior noise levels are some vital measures. One of the highest in-cabin noise levels now arises from heating, ventilating and air conditional (HVAC) systems. The HVAC noise is a common problem for most of the automotive manufacturers. In this study, the HVAC noise problem is investigated for Proton Exora vehicle. Proton Exora is a multi-purpose type vehicle (MPV) which induced a considerable HVAC noise level compared to the other Proton vehicles. Regarding to this issue, this study aims to investigate the source of the HVAC noise for both vehicle and system level by a proper characterization of the noise and vibration patterns of the vehicle HVAC system under various operating system. First, the study is carried out for vehicle level where the noise and vibration of HVAC system are measured and analysed directly on real car. Whereas for system level, a test rig is developed specifically to assemble a complete HVAC system exactly as in vehicle level. All the assembly unit and components such as compressor, condenser, thermal expansion valve (TXV), evaporator, blower, air conditioner pipe, and related hose is supplied to USM by PROTON. An electric motor being used to drive the compressor pulley to run the whole HVAC system. For measurement of noise and vibration, microphone and accelerometer sensors is used by locating all of them at related components to be analysed. Test conducted under two patterns of car in idle and by elevated speed or rpm tracking where tachometer is used to measure the engine speed. From data collected, analysis is made includes the spectrum analysis and order analysis. Later, verification is made by noise detection from real time vibration and noise data using sound diagnosis from LMS Test.Lab software. In addition, with the aid from sound camera, source of noise at related components and parts can be located. After determining the source and type of noise such as hissing, humming, clicking, and rush noise from the HVAC system, a proper justification is made regarding the generation of noise from related components involved and how they operate. Main contributors from each type of HVAC noise is identified for design solution and countermeasure to be proposed in future. This would be taken as refinement initiative to improve current design guideline for HVAC system in order to come out with HVAC system exhibits low noise level for a better passenger in cabin comfort and experience.